VIDEO CHAT APPLICATIONS (VCA) IN ENHANCING STUDENTS’ ENGLISH COMMUNICATION SKILLS AT POLITEKNIK UNGGUL LP3M MEDAN - Hermansyah, Hermansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The objective of this study is to evaluate how well the use of VCA in enhancing English communication skills for students at Politeknik Unggul LP3M. Pre-experimental research design and quantitative research methodology are both employed in this study. There were 48 Politeknik Unggul LP3M students enrolled in classes AK4A/21 and AP4C/21 during their 4th semester served as the subjects of this study. A speaking test and a TOEIC test were administered both before and after the VCA as the research instrument. SPSS Ver. 21 was used for the quantitative analysis of the data. The findings of this study indicate that students scored higher on the post-test (12.79)/ (680) than the pre-test (5.66) of both the speaking test and TOEIC test. With respect to the t-test, the significant level (p) of 5%, as well as the t-test value (21.710) is greater than the t-table value (3.138) with the df (47) and the significance of two-tailed (0.000 < 0.05). It implies the acceptance of the Alternative Hypothesis (Ha) and the rejection of the Null Hypothesis (Ho). Eventually it can be concluded that the usage of VCA can enhance students’ communication skills significantly.